2001
DOI: 10.4067/s0716-10182001000200004
|View full text |Cite
|
Sign up to set email alerts
|

Patrones de sensibilidad in vitro y comportamiento clínico de Shigella

Abstract: Las infecciones por Shigella se mantienen como un problema de salud pública en el panorama mundial, asociándose a bajo nivel de vida en países en desarrollo 1 y a grupos de riesgo o EXPERIENCIA CLINICA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…Studies from many regions of Chile have already reported an increase in isolation of Shigella that are resistant or exhibiting multi-resistance to clinically important and commonly used antibiotics. [8][9][10] Our findings from the semirural study area of Colina, are consistent with those reports in that we also observed an alarmingly high prevalence of Shigella that are resistant to antibiotics frequently used for treating shigellosis by clinicians in Santiago.…”
Section: Discussionsupporting
confidence: 91%
“…Studies from many regions of Chile have already reported an increase in isolation of Shigella that are resistant or exhibiting multi-resistance to clinically important and commonly used antibiotics. [8][9][10] Our findings from the semirural study area of Colina, are consistent with those reports in that we also observed an alarmingly high prevalence of Shigella that are resistant to antibiotics frequently used for treating shigellosis by clinicians in Santiago.…”
Section: Discussionsupporting
confidence: 91%
“…Shigella flexneri y S. sonnei son las especies prevalentes y endémicas en América Latina y en países industrializados 7 . En Chile, S. flexneri y S. sonnei, constituyen más de 80% de las cepas de Shigella aisladas, con una proporción similar entre ambas, predominando S. sonnei cada dos o tres años [8][9][10] . Investigaciones realizadas en niños chilenos, mostraron que un número reducido de serotipos (S. sonnei, S. flexneri 2a, S. flex-…”
Section: En Base Al Antígeno O Del Lipopolisacárido (Lps) Enunclassified
“…Studies from many regions of the world have already reported an increase in isolation of S. flexneri that are multidrug resistant to clinically important and commonly prescribed antibiotics. [13][14][15] In the current study, 110 liquid stool samples were examined by direct culture on selective media-yielded Shigella species. It was further tested to confirm species identification by VITECK ® 2 system.…”
Section: Discussionmentioning
confidence: 99%